IN-SITU X-RAY TRANSMISSION POWDER DIFFRACTION STUDY OF THE KINETICS OF THE LIGHT INDUCED ALTERATION OF REALGAR (α-AS4S4 - Ballirano P.; Maras A. (My University, 2006)
An in-situ X-ray transmission powder diffraction study of the kinetics of the light induced alteration of realgar (As4S4) has been carried out. Data indicate that the crystalline final products of the process are pararealgar (different As4S4 polymorph) and arsenolite (As2O3). Because of the chemical unbalance the evolution of SOx, is hypothesized. In fact there are no evidences of the presence of amorphous As-S alloys or amorphous S. The alteration proceeds via the occurrence of an intermediate term along the β-As4S 4-alacranite series joint with an estimated As4S 4.2 composition. This phase reach a maximum wt. fraction of ca. 30 % in the early stages of the process and subsequently disappears. From the fraction X(t) of realgar and pararealgar transformed vs. time was determined the kinetic law of the digestion of realgar and formation of pararealgar according to the JMAK model. The refined n ; parameters indicate that the behavior of the two transformations is intermediate between that of a diffusion-controlled and a first-• order model. The increased expansion of the realgar cell during the alteration could be possibly due to the requirement that structural coherency between at least two of the three sulfide phases is preserved. In particular the coherency between realgar and β-As4S4 is expected to exist along arcaIgar*sin β and C βAsS4 respectively. According to our data we may hypothesize that the light induced alteration of realgar to pararealgar occurs via an intermediate As4S4+x product because it is able to sustain the presence of As4S5-type cages. Following the model proposed by Kyono et al. (2005) the As4S5 cage release the extra S atom to form the As4S4 cage of pararealgar-type promoting the development of a new As4S cage in a cyclic process. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: β-AS4S4; ALTERATION; ARSENOLITE; PARAREALGAR; REALGAR; RIETVELD METHOD; SULFIDE PHASES; X-RAY POWDER DIFFRACTION